Malcolm McDonald on marketing planning : understanding marketing plans and strategy - McDonald, Malcolm (United Kingdom ; New York : Kogan Page, 2017)
"A primer for marketing professionals and students, the second edition of Malcolm McDonald on Marketing Planning focuseson the practical application of marketing planning. Chapters explainadvertising and sales promotion strategies,price and sales strategies, how to define markets and segments, andhow to set marketing objectives and strategies. This fullyrevised second edition has not only been updated to contain the latest research, but also includes an extensive appendix covering topics such asdigital marketing, advertising, developing new products, and international product planning"--
"A primer for marketing professionals and students, the second edition of Malcolm McDonald on Marketing Planning provides a clear guide to marketing planning. Focussing on the practical application of marketing planning this book will guide readers through the production of a marketing plan that has real world application. Key content includes defining markets and segments, setting marketing objectives and strategies, advertising and sales promotion strategies, and price and sales strategies. With an emphasis on practicality this fully revised second edition has been thoroughly overhauled to contain new content on the essentials of marketing planning and the strategic marketing process"--
Revised edition of the author's Malcolm McDonald on marketing planning, 2008.
Includes bibliographical references and index.
Keywords: Marketing -- Planning; Marketing -- Management; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Strategic Planning